Implementasi Program P5 Pada Kurikulum Merdeka Belajar Dalam Pembentukan Karakter Peserta Didik di SMAN 2 Bengkalis - Anggraini, Desta; Anisa, Nanda (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to determine the Implementation of the Project Program to Strengthen Pancasila Student Profiles in the Independent Learning Curriculum in the Formation of Student Character at SMAN 2 Bengkalis. This research is included in the category of qualitative research using a descriptive analysis approach. The data collection technique is carried out through three series of activities, namely observation, interviews and documentation. The data analysis technique used is the Milles and Huberman model which also summarizes three important points, namely data reduction, data presentation and drawing conclusions. The results showed that the Implementation of the P5 program in the Independent Learning Curriculum in Forming Student Character at SMAN 2 Bengkalis went well. The selection of activity themes is considered capable of growing the six character dimensions listed in the P5 program. This can be proven from the high enthusiasm of educators and students during the project. Both parties work together in the success of the program, especially students who hold the main key to project success